2019
DOI: 10.1017/s0960258519000205
|View full text |Cite
|
Sign up to set email alerts
|

Masting and regeneration dynamics of Abies cephalonica, the Greek endemic silver fir

Abstract: Masting and regeneration dynamics were investigated in a long-term perspective using Abies cephalonica as a study tree species. Extensive fieldwork was implemented in Parnitha National Park, Greece, following a large-scale wildfire. Annual cone production was monitored for a 5-year period in 130 tagged trees, in 13 plots with 10 individuals each, established both within the unburned part of the forest and in surviving fragments of the burned area. In the most recent masting year, a high percentage (88%) of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although Koutavas [78] reports a growth acceleration of the species since the 1990s, potentially related to CO 2 fertilisation, simulations with vegetation dynamics models (that did not, however, account for CO 2 fertilisation) suggest that under drier conditions, A. cephalonica might be replaced by more drought-resistant species [12]. Other studies have shown that A. cephalonica regeneration is controlled by regional climatic conditions [79], fire [80] and the distance from unburned patches [76], suggesting that under more fire-prone conditions, the species might fail to regenerate. Overall, our findings, combined with previous work, suggest that the vulnerability of the endemic A. cephalonica to climate change could be highly regulated by local weather conditions and the interplay with fire regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Although Koutavas [78] reports a growth acceleration of the species since the 1990s, potentially related to CO 2 fertilisation, simulations with vegetation dynamics models (that did not, however, account for CO 2 fertilisation) suggest that under drier conditions, A. cephalonica might be replaced by more drought-resistant species [12]. Other studies have shown that A. cephalonica regeneration is controlled by regional climatic conditions [79], fire [80] and the distance from unburned patches [76], suggesting that under more fire-prone conditions, the species might fail to regenerate. Overall, our findings, combined with previous work, suggest that the vulnerability of the endemic A. cephalonica to climate change could be highly regulated by local weather conditions and the interplay with fire regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Sites that were not fir dominated prior to fire proved unsuitable also for planting fir seedlings. A minor part of the observed variability could be associated with the initial height of seedlings, especially for seedlings showing high rates of apical growth.Land 2020, 9, 100 2 of 15 increased thereafter [6]. The species is not linked to specific soil conditions [7] and the flora of the stands is related to drought stress.…”
mentioning
confidence: 99%
“…Land 2020, 9, 100 2 of 15 increased thereafter [6]. The species is not linked to specific soil conditions [7] and the flora of the stands is related to drought stress.…”
mentioning
confidence: 99%
“…These changes in vegetation type can be attributed either to anthropogenic factors or changes in climatic conditions and are characteristic examples of forest degradation. In the southern parts of the Greek fir's distribution, seedlings establish predominantly under the shade of adult trees [33,34]. The removal of vegetation along with grazing can negatively affect tree seedling establishment and result in an expansion of shrublands and grasslands in previously tree-dominated areas.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that black pine is currently more widespread in the Peloponnese than it was in the early 19th century. Compared to Greek fir [34], black pine regenerates more effectively after wildfires and may return to its previous cover [37]. In addition, black pine is more drought tolerant than Greek fir and could have had displaced it due to changing climatic conditions [38].…”
Section: Discussionmentioning
confidence: 99%